Tenecteplase in Pulmonary Embolism Patients: A Meta-Analysis and Systematic Review - Zhang, Zhu; Xi, Linfeng; Zhang, Shuai; Zhang, Yunxia; Fan, Guohui; Tao, Xincao; Gao, Qian; Xie, Wanmu; Yang, Peiran; Zhai, Zhenguo; Wang, Chen (Frontiers in Medicine, 2022)
OBJECTIVE: To assess the efficacy and safety of tenecteplase in patients with pulmonary embolism (PE). METHODS: We completed the literature search on May 31, 2021 using PubMed, EMBASE and the Web of Science. Analyses were conducted according to PE risk stratification, study design and duration of follow-up. The pooled risk ratios (RRs) and its 95% confident intervals (CIs) for death and major bleeding were calculated using a random-effect model. RESULTS: A total of six studies, with four randomized controlled trials (RCTs) and two cohort studies, were included in this study out of the 160 studies retrieved. For patients with high-risk PE, tenecteplase increased 30-day survival rate (16% vs 6%; P=0.005) and did not increase the incidence of bleeding (6% vs 5%; P=0.73). For patients with intermediate-risk PE, four RCTs suggested that tenecteplase reduced right ventricular insufficiency at 24h early in the onset and the incidence of hemodynamic failure without affecting mortality in a short/long-term [<30 days RR=0.83, 95% CI (0.47, 1.46);≥30 days RR=1.04, 95% CI (0.88, 1.22)]. However, tenecteplase was associated with high bleeding risk [<30 days RR=1.79, 95% CI (1.61, 2.00); ≥30 days RR=1.28, 95% CI (0.62, 2.64)]. CONCLUSIONS: Tenecteplase may represent a promising candidate for patients with high risk PE. However, tenecteplase is not recommended for patients with intermediate-risk PE because of high bleeding risk. More large-scale studies focused on tenecteplase are still needed for PE patients.